Two new European species of the marine genus Tubificoides (Annelida: Clitellata: Naididae) with notes on the morphology of T. pseudogaster (Dahl, 1960) - Kvist, Sebastian; Erséus, Christer (Zootaxa, 2018)
Two new species of Tubificoides (subfamily Tubificinae), T. charlotteae n. sp. and T. mackiei n. sp., are described based on morphological analyses. Both species were flagged as potentially cryptic in a previous investigation, based on both mitochondrial and nuclear sequence data. Tubificoides charlotteae n. sp., known only from an intertidal site in southern Spain, is characterized by the lack of cuticular papillation, the possession of several needle-like hair chaetae in dorsal bundles, a cone-shaped penis sheath, and a rather large, muscular penial sac. It strongly resembles the north-west European, largely sublittoral species T. amplivasatus, but differs from this species in terms of body size, width of vas deferens, and the shape and size of both the ejaculatory duct and penial sac. Tubificoides mackiei n. sp., collected from the southeast coast of Norway and the west coast of Sweden, is characterized by the lack of cuticular papillae and hair chaetae, and the possession of a rather long penis sheath with a wide terminal opening. It shares several morphological features with the sympatric species Tubificoides pseudogaster, but is distinguished from the latter by the detailed morphology and length of the penis sheaths, the width of the atrium, and the lower maximal number of bifid chaetae in dorsal preclitellar bundles. The utility of an integrative comparative approach, combining molecules and morphology, for the identification and delineation of new taxa within Tubificoides is briefly discussed.